Biology teaching material needs analysis based on cooperative learning approaches in the human physiology system - Dwi Candra Setiawan; Mila Karmila; Anastasia Pitung; Gloria A. N. Daga Dede (JPBIO (Jurnal Pendidikan Biologi), 2020)
This research was conduct because of the low development of teaching material made by educators. The development of a teaching material that is by the character and background of students is necessary to be able to facilitate students in the learning process. This study aims to obtain preliminary data to develop a teaching material based on a cooperative approach to the material system of human physiology. This research is a qualitative descriptive study. The population used is high school students in Malang with 75 research samples taken from three schools. Random sample selection by giving an open questionnaire. Data collection techniques were carried out by observation, questionnaire distribution, and interviews. The data obtained were analyzed through descriptive analysis. From the results obtained from the needs analysis test, 98% of students expect the development of a teaching material that can help students understand the topic of the human physiology system by developing teaching materials based on a cooperative approach.Keywords: Teaching materials, cooperative learning, human physiology system